Pacific university graduates in New Zealand: what helps and hinders completion. (June 2018) - Theodore, Reremoana; Taumoepeau, Mele; Tustin, Karen; Gollop, Megan; Unasa, Charlotte; Kokaua, Jesse; Taylor, Nicola; Ramrakha, Sandhya; Hunter, Jackie; Poulton, Richie
Increasing the numbers of Pacific Island students who graduate from New Zealand universities is important for the students' futures, their families, communities and society in general. In this study, Pacific graduates ( N  = 365) who are participants in the Graduate Longitudinal Study New Zealand were asked to describe what factors helped or hindered their qualification completion. Graduates from all eight New Zealand universities were surveyed between July and December 2011. Pacific graduates identified external (e.g. family), institutional (e.g. university staff) and student or personal (e.g. motivation) factors that both helped and hindered the successful completion of their studies. Understanding the hindrance factors faced by Pacific students and the factors that have contributed to their educational success can help to inform policy and practice to achieve national priorities of equity and successful outcomes for Pacific learners.